2017
DOI: 10.5897/jvmah2016.0525
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and the history of Echinococcus granulosus infection in dogs within the past few decades in Libya: A review

Abstract: Echinococcus granulosus is a tiny tapeworm that parasitizes the small intestine of canids, mainly dogs, which act as definitive hosts for the parasite. Infected dogs are the main source of infection to humans and livestock which act as intermediate hosts resulting in hydatid disease condition. E. granulosus is widely distributed in many parts of the world, and is very common in North African countries. In Libya, the rate of infection with echinococcosis in dogs was reported to be lower than 7 to 80% in stray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…prevalence in the target population was 5.5%, which is similar to what was observed in Kosovo [29]. Higher prevalence was reported in the same target population in Uganda [7], Libya [30], China [12], Turkey [31], and Morocco [6], whereas no evidence of E. granulosus was detected among owned dogs in Germany and other European countries [32]. The E. granulosus prevalence in dogs that we observed in Nigeria is in agreement with a recent meta-analysis study that reported markedly lower values in West Africa (5.5%) compared to East (23.4%) and North Africa (24.7%) [33].…”
Section: Discussionsupporting
confidence: 83%
“…prevalence in the target population was 5.5%, which is similar to what was observed in Kosovo [29]. Higher prevalence was reported in the same target population in Uganda [7], Libya [30], China [12], Turkey [31], and Morocco [6], whereas no evidence of E. granulosus was detected among owned dogs in Germany and other European countries [32]. The E. granulosus prevalence in dogs that we observed in Nigeria is in agreement with a recent meta-analysis study that reported markedly lower values in West Africa (5.5%) compared to East (23.4%) and North Africa (24.7%) [33].…”
Section: Discussionsupporting
confidence: 83%
“…The protoscolices evaginate, attach to the mucosal lining of their intestine and grow into the adult worms within 6 -8 weeks depending on the parasite strain and host sensitivity (Lightowlers et al 2003;Shnawa et al 2021). Adult worms remain alive in the final host for 5-20 months, then begin to release eggs or gravid segment every 2 weeks (Rahman et al 2015, Thompson et al 2017, Mohamed et al 2017Tse et al 2019).…”
Section: Life Cycle Of Echinococcus Granulosusmentioning
confidence: 99%
“…It is difficult to adjust the exposure to echinococcosis that due to difficulty in staying aloof from CE eggs which are transmitted with feces of wild animals causing recurrence of CE, on the other hand, it's difficulties in diagnosis because the disease in animals is asymptomatic [25,31]. However, control of hydatidosis depends on breaking the cycle of infection either by preventing definitive hosts (as dogs) from eating carcasses of infected intermediate hosts or by preventing intermediate hosts (as humans) from eating contaminant food by dog feces [7,32].…”
Section: Control and Preventionmentioning
confidence: 99%